Gender Violence in Public Spaces - Beatriz Arce, María (2015)
Gender-Based Violence (GBS) is one of the most important obstacles in theway to development. The model of communication for social change (C4SC),under an approach of civil rights, presents an unavoidable opportunity for communicators to take over the urgent ethical demand of placing their work atthe service of public politics in order to fulfill this goal; but mainly in order tostrengthen the women agency in order to promote their empowerment. Herethe model of C4SC is overlaid on the case of sexual harassment on the streets,in order to identify the strategic lines that can be used for addressing other casesof gender-based violence.